Правила и составные части методики обобщенно-множественного отображения информации в подсистеме экспресс-анализа СППР аудита - Нескородева, Татьяна Васильевна (НТУ "ХПИ", 2017)
Определена информация синтетического учета характеризующая состояние и результаты деятельности предприятия за период проверки на верхнем уровне. Установлены взаимосвязи синтетического учета и характеристик предприятия как объекта управления. Формализованы функциональные зависимости, характеризующие взаимодействие переменных СППР аудита. Определены правила и свойства соответствия отображений множеств численных значений переменных как предварительный этап подготовки данных для аудита. На основании полученных результатов сформулирована сущность методики обобщенно-множественного отображения информации в СППР аудита.

The information of the synthetic account which characterizing a state and enterprise activity results for the check period on the top level is defined. The relationship between the synthetic accounting and the characteristics of the enterprise as an object of management is established. Functional dependencies which characterizing the interaction of the DSS audit variables are formalized. The rules and properties of sets mappings correspondence of numerical values of variables are defined as a preliminary stage of data preparation for audit. Based on the obtained results, the essence of the generalized-multiple information mapping technique in the DSS of the audit is formulated. The application of this technique will allow: to reduce the volume of analyzed multidimensional data or actual verification at lower levels by allocating equivalent subsets at the upper levels; use the results of a polyalternative analysis on a set of characteristics of data sets for preparing decision-making with polyalternative criteria for assessing the equivalence of sets in IT multi-level DSS audit; determine the reason for the lack of data equivalence, through the definition of functional relationships, the implementation of which does not correspond to the properties of mappings.
Rules and components of a generalized-multiple display method of information in the express analysis subsystem of the audit decision support system
Keywords: синтетический учет; информационная технология; деятельность предприятия; synthetic accounting; information technology